A city for Marc: an inclusive urban design approach to planning for adults with autism - Decker, Elizabeth Florence (Kansas State University, 2014)
The generation of diagnosed autistic children is aging, calling on needed research for what will happen to autistic adults. Cities are outfitted to non-autistic people, typically created for an idealized individual without disability or limitation. Urban environments add to sensory overload, have limited mass transit accessible to those with neurological disabilities, provide few affordable housing units, offer very little employment opportunity, and have no green spaces designed for those with autism or other differences. Typical urban design does not take into account the landscape and urban affordances needed by adults with autism. This project synthesizes a toolkit including the following needs for adults with autism: vocational training, life skills, mental and physical health support, employment, public transportation and affordable housing. Using the initial theoretical urban systems toolkit, I conducted an evaluation and synthesized proposal for Nashville, Tennessee, a large city that ranks within the nation among the lowest for cost-of-living (e.g. groceries, housing, and utilities). The outcome of the evaluation and synthesis is a diagrammatic infographic conveying existing and needed services within Nashville, as well as connectivity of needs for adults with autism. From the diagrammatic proposal, the initial theoretical urban systems toolkit is revised, reflecting upon the findings through the evaluation of Nashville, Tennessee. The final theoretical urban systems toolkit and diagrammatic proposal for Nashville, Tennessee provides exploratory research for city planners, architects, and landscape architects to design for cities inclusive of adults with autism, as well as other neurological disabilities or limitations. This additional layer of design not only contributes to the social and environmental well-being of individuals with autism, but also contributes to the entire urban community. Urban design as an approach to planning for adults with autism contributes a new disciplinary perspective to the discourse on planning for a maturing autistic population.
Keywords: Urban design; Inclusive city; Adults with autism; Urban design systems toolkit; Urban affordances; Landscape affordance network; Landscape Architecture (0390)